Step-by-step explanation:
X(x+6) - 6(x+6)
X+6x-6x-36
X-36
Take the derivative:
g’(x) = 12x^3 - 24x^2
Set equal to zero and solve:
0 = 12x^3 - 24x^2
0 = 12x^2 (x - 2)
x = 0 or x = 2
Plug back into original
g(0) = 3(0^4) - 8(0^3)
g(0) = 0 - 0
g(0) = 0
g(2) = 3(2^2) - 8(2^3)
g(2) = 3(4) - 8(8)
g(2) = 12 - 64
g(2) = -52
There is an absolute max at (0,0) or when x = 0
Answer:
-7 < -5
Step-by-step explanation:
-5 is greater than -7
Make improper fractions.
33/5 - 43/10
Find a common denominator, in this case it is 10.
66/10 - 43/10 = 23/10
This can be simplified to 2 3/10
Hope this helps!
Answer:
7x12x2=168 I think but how did u do this